On Taungurung Land Sharing History and Culture - Jones, Jennifer (Aboriginal History Monographs, 2020)
On Taungurung Land: Sharing History and Culture is the first monograph to examine how the Taungurung Nation of central Victoria negotiated with protectors and pastoralists to retain possession of their own country for as long as possible. Historic accounts, to date, have treated the histories of Acheron and Mohican Aboriginal stations as preliminary to the establishment of the more famous Coranderrk on Wurundjeri land. Instead of 'rushing down the hill' to Coranderrk, this book concentrates upon the two foundational Aboriginal stations on Taungurung Country. A collaboration between Elder Uncle Roy Patterson and Jennifer Jones, the book draws upon Taungurung oral knowledge and an unusually rich historical record. This fine-grained local history and cultural memoir shows that adaptation to white settlement and the preservation of culture were not mutually exclusive. Uncle Roy shares generational knowledge in this book in order to revitalise relationships to place and establish respect and mutual practices of care for Country.